En route to photoaffinity labeling of the bacterial lectin FimH - Thisbe K. Lindhorst; Michaela Märten; Andreas Fuchs; Stefan D. Knight (Beilstein Journal of Organic Chemistry, 2010)
Mannose-specific adhesion of Escherichia coli bacteria to cell surfaces, the cause of various infections, is mediated by a fimbrial lectin, called FimH. X-ray studies have revealed a carbohydrate recognition domain (CRD) on FimH that can complex α-D-mannosides. However, as the precise nature of the ligand–receptor interactions in mannose-specific adhesion is not yet fully understood, it is of interest to identify carbohydrate recognition domains on the fimbrial lectin also in solution. Photoaffinity labeling serves as an appropriate methodology in this endeavour and hence biotin-labeled photoactive mannosides were designed and synthesized for photoaffinity labeling of FimH. So far, the photo-crosslinking properties of the new photoactive mannosides could be detailed with the peptide angiotensin II and labeling of FimH was shown both by MS/MS studies and by affino dot–blot analysis.